Sympathetic ophthalmia: A comprehensive update - Swapnil Parchand; Deepshikha Agrawal; Nikitha Ayyadurai; Aniruddha Agarwal; Anil Gangwe; Shashwat Behera; Priyavat Bhatia; Samyak Mulkutkar; Gulshan Barwar; Ramandeep Singh; Alok Sen; Manisha Agarwal (Indian Journal of Ophthalmology, 2022)
Sympathetic ophthalmia is a rare, bilateral, granulomatous, panuveitis following penetrating trauma or surgery to one eye. Clinical presentation commonly occurs within the first year of trauma occurrence but can be delayed by several years. It manifests as acute/chronic granulomatous uveitis with yellowish-white choroidal lesions or Dalen–Fuchs nodules. Initially, patients respond rapidly to corticosteroid therapy, but a majority require long-term use of corticosteroid-sparing agents to prevent recurrences. The purpose of this review is to elaborate on the current understanding of the pathophysiology, the importance of multimodal imaging in early diagnosis, and the role of newer immunomodulatory and biological agents in recalcitrant cases.